Trombocitopenia induzida por heparina em paciente com oclusão arterial aguda - Pimenta, Rafael Elias Farres [UNESP]; Yoshida, Winston Bonetti [UNESP]; Rollo, Hamilton Almeida [UNESP]; Sobreira, Marcone Lima [UNESP]; Bertanha, Matheus [UNESP]; Mariúba, Jamil Victor De Oliveira [UNESP]; Jaldin, Rodrigo Gibin [UNESP]; De Camargo, Paula Angeleli Bueno [UNESP] (FapUNIFESP (SciELO), 2016)
Heparin induced thrombocytopenia (HIT) is a serious complication of heparin anticoagulation and is associated with formation of anti-platelet factor 4. It usually occurs from the fifth day of treatment onwards, with a fall in platelet count of at least 50%. Venous or arterial thrombosis may occur as a result of concomitant platelet activation, with serious clinical repercussions. We present the case of a patient with antiphospholipid antibody syndrome who presented with acute arterial occlusion and was treated surgically and given unfractionated heparin intraoperatively and postoperatively. On the fifth day of anticoagulant treatment he exhibited a platelet count decreased by more than 50% compared to the count prior to heparin administration. The suspicion of heparin-induced thrombocytopenia and its diagnostic and therapeutic features are addressed in this therapeutic challenge paper.
Heparin induced thrombocytopenia in a patient with acute arterial occlusion
Keywords: Diagnosis and therapy; Heparin; Thrombocytopenia; Thrombophilia